Mitochondrial alterations and apoptosis in smooth muscle from aged rats - Lopes, G. S.; Mora, O. A.; Cerri, P.; Faria, F. P.; Jurkiewicz, N. H.; Jurkiewicz, A.; Smaili, S. S. (Elsevier B.V., 2004)
We studied changes in mitochondrial morphology and function in the smooth muscle of rat colon. Under confocal microscopy, tissues loaded with potentiometric dye displayed rapid and spontaneous depolarization. Cyclosporin A (CsA), inhibitor of the permeability transition pore (PTP), caused an increase in mitochondrial membrane potential (DeltaPsi(m)) in tissues from adult young animals. In aged rats these changes were not observed. This suggests that physiological activation of PTP in aged rats is reduced. Electron microscopy showed alterations of the mitochondrial ultrastructure in tissues from aged rats involving a decreased definition of the cristae and fragmentation of the mitochondrial membranes. We also detected an increase in apoptotic cells in the smooth muscle from aged animals. Our results show that the aging process changes PTP activity, the ability to maintain DeltaPsi(m) and mitochondrial morphology. It is suggested that these can be associated with mitochondrial damage and cell death. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: mitochondria; calcium; smooth muscle; aging; mitochondrial dysfunction